Aerobic and anaerobic effect of CrossFit training: A narrative review - Moscatelli, F.; Messina, G.; Polito, R.; Porro, C.; Monda, V.; Monda, M.; Scarinci, A.; Dipace, A.; Cibelli, G.; Messina, A.; Valenzano, A. (SportMont, 2023)
CrossFit is recognized as one of the fastest growing modes of high-intensity functional training. This strength and conditioning program is used to optimize physical competence in ten fitness domains: (1) cardiovascular/respiratory endurance, (2) stamina, (3) strength, (4) flexibility, (5) power, (6) speed, (7) coordination, (8) agility, (9) balance, and (10) accuracy. The aim of this review is to provide an overview related to Crossfit and its implication in aerobic and anaerobic parameters. Specifically, in this work, we will discuss the impact that this type of physical activity can have on a physiological level. Furthermore, the tools will be provided to understand how, by modulating the intensity, one can have benefits at an aerobic and anaerobic level. We will also review studies using CF as a resistance training methodology and finally discuss the findings of the various studies and provide recommendations for future studies.